Hubungan Diet Tinggi Lemak dengan Kejadian Akne Vulgaris pada Siswa SMKN Tanjungsari Lampung - Andre Giovanni; Hernowo Anggoro Wasono; Nopi Sani; Resati Nando Panonsih (ARTERI : Jurnal Ilmu Kesehatan, 2020)
Acne vulgaris is a common skin disease that occurs mainly in adolescents about 15-18 years. Acne vulgaris is marked by various skin disorders such as blackheads, papules, pustules, nodules, and scarring. Sebum produced by the palette gland is an essential factor for acne vulgaris. One of the risk factors is food, which is a high-fat diet. This study aims to determine the relationship between a high-fat diet with acne vulgaris to the students in Tanjungsari public vocational high school South Lampung 2020. This study uses an analytic survey with a cross-sectional method. Samples were taken using proportionate stratified random sampling with 90 students in Tanjungsari public vocational high school South Lampung as a research subject. Data collection by survey method is interview and observation using 3x24 hours food recall, direct examination using a loop, and absent list of students in grades 10-12. This study uses univariate analysis and bivariate analysis with the Chi-Square test. This research results from 90 subjects who found that females by 47 subjects (52,2%) and males by 43 subjects (47,8%). Subjects eating a high-fat diet are the most experienced with acne vulgaris by 42 subjects (82,4%) and didn’t experience acne vulgaris by 9 subjects (17,6%). Chi-Square test analysis results obtained p-value = 0,000 (p ≤ 0.05), which means a significant relationship between a high-fat diet with acne vulgaris. There is a meaningful relationship between a high-fat diet with acne vulgaris to students in Tanjungsari public vocational high school South Lampung 2020 (p ≤ 0,05).